HISTÓRIA EVOLUTIVA DE Achyrocline flaccida (WEINM.) DC. NO SUL DA MATA ATLÂNTICA - PILATI, LAURA (2020)
The Atlantic Forest (AF) is one of the most biodiverse biomes in Brazil, due in part to its wide variation in latitude. This variation allows different niches shaped by different climatic conditions. One of the vegetation formations in the southern region of AF is the Araucaria Forest that occurs in association with large areas of grasses known as "Campos". Phylogeographic studies with species from the central and northern regions of AF show that the climatic oscillations of the glacial periods of the Pleistocene influenced the pattern of distribution and structuring of species. In the south of AF during the last ice ages, climatic conditions seem to have favored the expansion of grass areas, in contrast, the Araucária Forests that were restricted to refuges in the river valleys. Studies have shown that rivers and their valleys have acted as geographical barriers in structuring species. There are few studies in the literature related to the evolutionary history of species adapted to colder climatic conditions occurring in the southern regions of AF, as well as the role of these possible barriers in the expansion of these populations. Achyrocline flaccida (Weinm.) DC. popularly known as macela, is a species widely distributed in the grassy areas of southern AF and adapted to the cold climate, therefore, the evaluation of the genetic structure of its populations may provide important data on the influence of Pleistocene climatic oscillations on the structure of these populations, as well as, contribute to the understanding of the evolutionary history of the vegetation of AF. In this study, eight populations of A. flaccida collected in the southern region of AF were evaluated, four of which were collected in the north of the Uruguay river valley and four in the south. The intergenic chloroplast regions trnL-trnF and psbA-trnH and the nuclear DNA region (nDNA) ITS 4 and 5 were sequenced. The concatenated sequences for the two chloroplast regions generated a fragment of 1264 bp and the analysis of all sequences obtained identified 61 haplotypes. The nDNA sequences were 674 bp length and generated 47 ribotypes. The populations showed high nucleotide and haplotypic diversity. The neutrality and Bayesian Skyline Plot tests showed that there was a slight population expansion, in a period of colder climate, during the penultimate glacial maximum (210-140 thousand years ago), followed by stability in population size until the Holocene. The statistical significance of the SSD and HRAG indexes did not validate the multimodal pattern presented by the mismatch distribution charts, corroborating the population expansion observed around 200 thousand years ago. A high phylogeographic structure for A. flaccida and a high number of exclusive haplotypes and ribotypes were observed in populations north and south of the Uruguay river valley. All the data obtained corroborate that the Uruguay river valley may have acted as a geographical barrier limiting the gene flow between the populations of macela in southern AF. Also, the high diversity of populations and population stability during the Pleistocene shows, as observed for other species, the existence of large areas of occurrence of cold-climate species in southern Brazil during the last glacial periods.